Model Matematika Terhadap Penyebaran Penyakit Tuberkulosis di Rumah Sakit Paru Batu - Fitria, Vivi Aida (Jurnal Ilmiah Teknologi Informasi Asia, 2011)
Mathematical models for the spread of tuberculosis is a reference to the mathematical modeling of mechanisms of the spread of tuberculosis in the form of systems of differential equations is not linear. Particularly at the Hospital of Lung Batu.Penelitian aims to determine the modeling of the spread of tuberculosis to the system of differential equations and to find out the analysis of mathematical models of the spread of tuberculosis. These results indicate that the mathematical modeling of the spread of tuberculosis has three differential equations are not linear (1) the number of people susceptible tuberculosis at the time t (S (t)) in this case is the number of employees and aircraft hospitalization (excluding patients with TB) , (2) the amount of latent human tuberculosis (infected but not contagious, TB passive) at the time t (L (t)), and (3) the number of people infected with tuberculosis (infected and infectious, active) at time t (I (t) ). And of the system obtained two fixed points which is a fixed point of the first to show that all human beings are both healthy and potentially infected with tuberculosis (global stability)